EFFECT OF STATINS ON SERUM CONCENTRATION OF INFLAMMATORY MARKERS AND MATRIX METALLOPROTEINASES IN PATIENTS WITH ACUTE ST-SEGMENT ELEVATION MYOCARDIAL INFARCTION - TAMARA B. Pecherina; OLGA V. Gruzdeva; OLGA L. Barbarash (Фундаментальная и клиническая медицина, 2019)
Aim. To assess the effect of pre-hospital administration of statins on the levels of inflammatory markers and matrix metalloproteinases in the se-rum of patients with acute ST-segment elevation myocardial infarction (STEMI).Materials and Methods. We consecutively recruited 175 patients with STEMI (116 (66.3%) men and 59 (33.7%) women, average age 61.3 ± 8.4 years). Serum concentrations of interleukins (IL-6, IL-10, IL-12), C-reactive protein (CRP), tu-mor necrosis factor-α (TNF-α), and matrix metal-loproteinases (MMP-1, -3, -9) as well as blood lipid parameters were evaluated in all patients at the admission and on 12th day after STEMI onset. All the patients were divided into 2 groups depending on pre-hospital use of statins: 136 (77.71%) patients without and 39 (22.29%) patients with statin administration.Results. As compared to the patients without prior statin treatment, those who used statins ≥ 7 days prior to the development of STEMI had significantly lower values of serum low-density lipoproteins [2.91 (1.31; 5.13) vs 1.34 (0.76; 9.77), respectively], IL-6, CRP, TNF-α, and MMP-9 at both time points. In keeping with these ndings, serum level of anti-inflammatory marker IL-10 was two-fold higher in patients taking statins at the pre-hos-pital stage in comparison with those without statin administration. Conclusions. The lack of pre-hospital statin administration in patients with STEMI is associated with the higher values of pro-inflammatory markers (IL-6, CRP, TNF-α), and MMP-9 during in-hospital period.